2005
DOI: 10.1212/01.wnl.0000148600.60470.e6
|View full text |Cite
|
Sign up to set email alerts
|

An autosomal recessive cerebellar ataxia syndrome with upward gaze palsy, neuropathy, and seizures

Abstract: The authors describe three siblings born to consanguineous parents with early onset ataxia, dysarthria, myoclonic, generalized tonic clonic seizures, upward gaze palsy, extensor plantar reflexes, sensory neuropathy, and normal cognition. Direct screening excluded mutations in FRDA, TDP1,and SACS genes and at 8344, 3243, and 8993 positions of mitochondrial DNA. Linkage analysis excluded AOA-1, EPM1, EPM2A, EPM2B, CAMOS, and recessive ataxias linked to chromosome 9q34-9qter. This clinical constellation may repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Three pedigrees resembling ULD, with relatively earlier age at onset, no major cognitive decline, and upward gaze paralysis in some affected members, without CTSB mutations, were reported11, 12; a homozygous mutation in PRICKLE1 (12p11‐q13) was recently found in these families 13. LD is caused, in 58% of cases, by mutations in EPM2A (6q23‐25), encoding laforin dual‐specificity phosphatase and, in 35% of cases, by mutations in EPM2B (6p22.3), codifing malin ubiquitin E3 ligase 14, 15.…”
Section: Discussionmentioning
confidence: 99%
“…Three pedigrees resembling ULD, with relatively earlier age at onset, no major cognitive decline, and upward gaze paralysis in some affected members, without CTSB mutations, were reported11, 12; a homozygous mutation in PRICKLE1 (12p11‐q13) was recently found in these families 13. LD is caused, in 58% of cases, by mutations in EPM2A (6q23‐25), encoding laforin dual‐specificity phosphatase and, in 35% of cases, by mutations in EPM2B (6p22.3), codifing malin ubiquitin E3 ligase 14, 15.…”
Section: Discussionmentioning
confidence: 99%
“…In one family, the patients were adolescents and adults exhibiting primarily a PME, so closely resembling Unverricht's disease that it was called EPM1B (Berkovic et al, 2005). In the other two families, the affected individuals were children manifesting an ataxia (Straussberg et al, 2005;El-Shanti et al, 2006). A collaborative reevaluation of the families showed that two shared the same last name, that the children who had presented with ataxia were exhibiting myoclonus as they grew older, and that the adolescents and adults with myoclonus had in fact had ataxia earlier in life.…”
Section: Ataxia-pme Diseasementioning
confidence: 99%
“…MRI shows no atrophy even of the cerebellum. Peripheral tissues exhibit no inclusions material, and brain has not yet been studied (Berkovic et al, 2005;Straussberg et al, 2005;El-Shanti et al, 2006;Bassuk et al, 2008).…”
Section: Ataxia-pme Diseasementioning
confidence: 99%
“…Several genome-wide scans for linkage have been reported with various versions of the 10K array [22][23][24][25][26][27][28][29][30][31][32][33]. John and coworkers compared a genome-wide scan using microsatellites at 10-cM resolution against the 10K array in 157 rheumatoid arthritis families [22].…”
Section: Linkagementioning
confidence: 99%
“…Therefore, a platform that combined both approaches by supplementing the use of SNPs with high-resolution, locus-specific oligos could offer the best long-term solution for this application. Several authors have demonstrated the potential advantages of performing linkage using SNP arrays compared with microsatellites [22][23][24][25][26][27][28][29][30][31][32][33]. Not only are the data collected more efficiently (cheaper and quicker), but the information content and resolution of 4000-10,000 SNPs is higher than that of 300 microsatellites.…”
Section: Expert Commentarymentioning
confidence: 99%